Efektivitas Komunikasi Persuasif Dalam Menarik Minat Konsumen Untuk Meningkatkan Penjualan Produk PT. Surya Artha Komputama Melalui Hostlive - Andinsyah Adi Putri; Delmarrich Bilga Ayu P; Rini Ganefwati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
As digital business competition intensifies, every company must adapt its communication strategy to be more adaptive to changes in consumer behavior.mThe purpose of this study is to determine the effect of persuasive communicationmon sales volume through consumer purchasing interest at PT. Surya Artha Komputama. This study employed a quantitative approach with a causal associative approach. The sample consisted of 80 consumers of PT. Surya Artha Komputama. Data collection involved an online questionnaire distributed using Google Forms. Partial Least Squares (PLS) was used for data analysis. The results of this study indicate that: (1) Persuasive communication has a significant effect on Purchase Interest at PT. Surya Artha Komputama; (2) Persuasive communication has a significant effect on Sales Volume at PT. Surya Artha Komputama; (3) Purchase Interest has a significant effect on Sales Volume at PT. Surya Artha Komputama.